1995
DOI: 10.1111/j.1440-1681.1995.tb02906.x
|View full text |Cite
|
Sign up to set email alerts
|

Animal Models of Vascular Dementia With Emphasis on Stroke‐prone Spontaneously Hypertensive Rats

Abstract: 1. Two experimental models designed to reflect different aspects of vascular dementia (rats with cerebrovascular occlusion and rats with cerebral embolization) and stroke-prone spontaneously hypertensive rats (SHRSP) have been evaluated. The focus was on SHRSP as a model for vascular dementia.2. Neuropathological data revealed that the cerebrovascular disorder in SHRSP was associated with lesions in their brains similar to those seen in typical human cases of multiple cerebral infarction.3. SHRSP that died fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
0

Year Published

2002
2002
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(27 citation statements)
references
References 7 publications
0
27
0
Order By: Relevance
“…SHRSP is an animal model of human cerebrovascular disease: as in the case of humans, these rats exhibit severe hypertension and spontaneously occurring strokes (Okamoto et al, 1974, Yamori et al, 1976, Saito et al, 1995, Sakurai-Yamashita et al, 1997, Qiang et al, 1989. It was found that in SHRSPs, DND was induced in the CA1 subfield of the hippocampus by transient occlusion of the carotid arteries, i.e., 2-VO (Yamashita et al, 1993, Qiang et al, 1989, although in normotensive rats, DND was induced by transient occlusion of the carotid arteries following the permanent occlusion of the vertebral arteries, i.e., 4-VO and not 2-VO (Pulsinelli et al, 1979).…”
Section: Discussionmentioning
confidence: 99%
“…SHRSP is an animal model of human cerebrovascular disease: as in the case of humans, these rats exhibit severe hypertension and spontaneously occurring strokes (Okamoto et al, 1974, Yamori et al, 1976, Saito et al, 1995, Sakurai-Yamashita et al, 1997, Qiang et al, 1989. It was found that in SHRSPs, DND was induced in the CA1 subfield of the hippocampus by transient occlusion of the carotid arteries, i.e., 2-VO (Yamashita et al, 1993, Qiang et al, 1989, although in normotensive rats, DND was induced by transient occlusion of the carotid arteries following the permanent occlusion of the vertebral arteries, i.e., 4-VO and not 2-VO (Pulsinelli et al, 1979).…”
Section: Discussionmentioning
confidence: 99%
“…The dose of galantamine was titrated upward in 4-mg increments over a 6-week period (4,8,12,16,20, and 24 mg daily during weeks 1, 2, 3, 4, 5, and 6, respectively). The patients continued with their maintenance dose of galantamine (24 mg/day) for an additional 4.5 months.…”
Section: Methodsmentioning
confidence: 99%
“…As with AD, it appears that the underlying cause of cognitive decline in VaD (and, therefore, AD + CVD) is cholinergic dysfunction. Decreased acetylcholine levels and nicotinic receptor dysfunction have both been implicated in the development and progression of cognitive decline in animal and human studies of VaD [4][5][6][7][8][9][10][11]. Thus, it is reasonable to expect that drugs used to manage cognitive decline in patients with AD also may be useful in patients with AD + CVD.…”
Section: Introductionmentioning
confidence: 99%
“…8,9 SHRSP is also well known as an excellent model for subcortical vascular dementia accompanied by small-vessel pathology, because these rats show structural alterations of small cerebral arteries, 10 reduction in cerebral blood flow, 11 white matter lesions 12,13 and cognitive impairment. 14,15 We then examined differences in gene expression between microdissected hippocampal vessels with BBB impairment in SHRSP and those without the impairment in Wistar Kyoto (WKY) rats using a microarray assay and reported that the expression of osteopontin, a matricellular protein, was increased in BBB-damaged vessels in hypertensive SHRSP compared with that in vessels without BBB impairment in WKY rats. 16 The study also indicated that the immunoreactivity of osteopontin was present in perivascular ED1-positive macrophage/microglial cells and suggested the possibility that osteopontin might act as an inducible modulator of vascular remodeling, which likely restored BBB function in the damaged blood vessels.…”
Section: Introductionmentioning
confidence: 99%